Short text messages to encourage adherence to medication and follow-up for people with psychosis (Mobile.Net): randomized controlled trial in Finland - Välimäki, Maritta; Kannisto, Kati Anneli; Vahlberg, Tero; Hätönen, Heli; Adams, Clive E. (JMIR Publications, 2017)
Background: A text messaging service (short message service [SMS]) has the potential to target large groups of people with long-term illnesses such as serious mental disorders, who may have difficulty with treatment adherence. Robust research on the impact of mobile technology interventions for these patients remains scarce.